1994
DOI: 10.1128/iai.62.12.5647-5651.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cell-associated collagenolytic activity by group B streptococci

Abstract: Group B streptococci (GBS) are important pathogens in neonatal sepsis, pneumonia, and meningitis. The ability of GBS to invade the collagen-rich amniotic membrane of the placenta has been shown in vitro. In the presence of GBS, the collagen fibrils of the amnion appear disordered, suggesting a role for GBS in premature rupture of membranes. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis, Sephadex G-200 column chromatography, and gelatin zymograms were used in this study to characterize cell-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
(23 reference statements)
2
8
0
Order By: Relevance
“…Indeed, highly proteolytic strains of Enterococcus faecalis were reported to be more virulent than weakly proteolytic strains in a rabbit model of infective endocarditis (15). A cell-associated collagenase has also been detected in group B streptococci (18), and it hydrolyzes the same collagen analogs as the S. gordonii protease reported here does. In addition, proteases may be important in normal processing of other surface proteins of streptococci; for example, the glycosyltransferase of S. sanguis is converted from 174 to 156 kDa at the cell surface (12).…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, highly proteolytic strains of Enterococcus faecalis were reported to be more virulent than weakly proteolytic strains in a rabbit model of infective endocarditis (15). A cell-associated collagenase has also been detected in group B streptococci (18), and it hydrolyzes the same collagen analogs as the S. gordonii protease reported here does. In addition, proteases may be important in normal processing of other surface proteins of streptococci; for example, the glycosyltransferase of S. sanguis is converted from 174 to 156 kDa at the cell surface (12).…”
Section: Discussionsupporting
confidence: 74%
“…Enzyme purification. Intact cells of GBS were found to exhibit weak FALGPA-hydrolyzing activity, and in agreement with the results reported by Jackson et al (8), much higher activity was found in cell lysates. Enzyme was therefore purified from the lysate of a cell pellet obtained from 60 liters of a log-phase culture (A 650 ϭ 0.8) of strain 3502 of GBS, a serotype III strain that had been isolated from the blood of an infected infant.…”
supporting
confidence: 91%
“…The recent report by Jackson et al (8) of a collagenase produced by GBS appeared to be yet another example of the production of an enzyme of GBS capable of degrading a component of the extracellular matrix and, possibly, facilitating invasion. The investigators speculated that the enzyme might contribute to the premature rupture of membranes frequently associated with neonatal infections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Group B streptococci (Streptococcus agalactiae) have also been associated with PROM and subsequent neonatal sepsis, pneumonia, and meningitis. This organism produces an enzyme which is capable of hydrolyzing both amniotic collagen fibrils (25) and FALGPA (23,24).…”
Section: Diseases Associated With Collagenolytic Bacteriamentioning
confidence: 99%